The Trust Paradox: A Dual-Pathway Analysis of Digital Marketing's Impacts on Consumer Loyalty and Consumer Decision - Supatman, Ernando R.; Walean, Ronny Hansye; Mandagi, Deske W. (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
In contemporary digital markets, cultivating sustained customer loyalty and shaping purchasing decisions present significant strategic challenges for companies. This study investigates the impact of digital marketing on consumer decisions and loyalty in the financing industry in Indonesia, comparing the mediating mechanisms of brand engagement (affective pathway) and consumer trust (cognitive path). Using an explanatory quantitative approach on 265 respondents selected through purposive sampling, the data were analyzed with Structural Equation Modeling (SEM). The findings reveal that digital marketing significantly influences consumer decisions and loyalty, with brand engagement acting as a partial mediator, while consumer trust does not mediate significantly, uncovering a